Afterwork Concert No. 3, “Mit veränderten Reprisen” - Beghin, Tom (2024)
Koetshuis, Orpheus InstituutProgram:Mozart, Sonata in E-flat Major, K 282C. P. E. Bach, Sonata in D Minor, Wq 50/4Mozart, Sonata in G Major, K 283On clavichord (replica Saxon-style, ca. 1760) and fortepiano (replica Stein, 1788)
Abstract:Performing on clavichord and fortepiano, Tom Beghin explores a once lively practice of varying repeats through two sets of keyboard sonatas—for a total of twelve, to be digested in groups of three: CPE Bach’s Sechs Sonaten mit veränderten Reprisen, Wq 50 (1760) and Mozart’s six “Munich” Sonatas K 279–285 (1774–75).
FRIS
0
Keywords: Declassifying the Classics: Rhetoric, Technology, and Performance, 1750-1850